[Spichlerze "Miedź", "Oliwski", "Panna"] [aut. odb. Karol Nowaliński]. - Nowaliński, Karol (1935- ). (Karol Nowaliński, 1986)
Przedstawia spichlerze "Miedź", "Oliwski", "Panna" na Ołowiance, widok od strony Długiego Pobrzeża, ok. 1910 r.